‘What Happened to Me Does Not Define Who I Am’: Narratives of Resilience in Survivor Victim Impact Statements - Craig, Miltonette (Victims & offenders, 2024)
While research shows that “ideal victims” still receive more media coverage and more favorable depictions and results in the criminal justice system, it is not clear whether this is how victims of crime want to present themselves. We code and analyze the transcripts of 21 violence against women survivor victim impact statements (VIS) from YouTube videos, to assess how survivors present their victimization. While survivors of violence discuss their pain and trauma, they also call for better services and protection for other survivors, and attempt to bring awareness about the ubiquity of violence while motivating other survivors to come forward. Survivors rarely present themselves as stereotypically defined “ideal victims,” though in some cases, they do focus on their own blamelessness and the motherly, familial relationships that have been negatively impacted by their victimization. Though ideal victim presentation may be a rational response for those seeking justice from patriarchal legal institutions, survivors resist ideal victim presentations based on stereotypical notions of femininity, demonstrating that from their perspectives, hierarchies between “deserving” and “undeserving” victims may be dissipating.